What Was the Point of Equality?. Issue 3 (21st October 2021) - Bejan, Teresa M.
Abstract: Political theorists often turn to seventeenth‐century England and the Levellers as sources of egalitarian insight. Yet by the time the Levellers were active, the claim that human beings were "equal" by nature was commonplace. Why, in Leveller hands, did a long‐standing piety consistent with social hierarchy became suddenly effectual? Inspired by Elizabeth Anderson, this article explores what equality—and the related concept of parity—meant for the Levellers, and what "the point, " as they saw it, was. I argue that the Levellers' key achievement was subsuming a highly controversial premise of natural parity within the existing language of natural equality. This suggests that modern basic equality is the product of two, potentially contradictory, principles. This, in turn, has important normative, as well as historical and conceptual, implications for how theorists understand "the point" of equality for egalitarian movements today.